Three pools of zeaxanthin in Quercus coccifera leaves during light transitions with different roles in rapidly reversible photoprotective energy dissipation and photoprotection - Peguero-Pina, José Javier (Journal of experimental botany, 2013)
Under excess light, the efficient PSII light-harvesting antenna is switched into a photoprotected state in which potentially harmful absorbed energy is thermally dissipated. Changes occur rapidly and reversibly, enhanced by de-epoxidation of violaxanthin (V) to zeaxanthin (Z). This process is usually measured as non-photochemical quenching (NPQ) of chlorophyll (Chl) fluorescence. Using instrumentation for instantaneous leaf freezing, NPQ, spectral reflectance, and interconversions within the xanthophyll cycle with time resolution of seconds were recorded from Quercus coccifera leaves during low light (LL) to high light (HL) transitions, followed by relaxation at LL. During the first 30 s of both the LL to HL and HL to LL transitions, no activity of the xanthophyll cycle was detected, whereas 70-75% of the NPQ was formed and relaxed, respectively, by that time, the latter being traits of a rapidly reversible photoprotective energy dissipation. Three different Z pools were identified, which play different roles in energy dissipation and photoprotection. In conclusion, ΔpH was crucial to NPQ formation and relaxation in Q. coccifera during light transitions. Only a minor fraction of Z was associated to quenching, whereas the largest Z pool was not related to thermal dissipation. The latter is proposed to participate in photoprotection acting as antioxidant